The effect of selective phosphodiesterase inhibitors, alone and in combination, on a murine model of allergic asthma - Clayton, Robert A (BioMed Central, 2004)
BACKGROUND: The anti-inflammatory effects of the selective phosphodiesterase (PDE) inhibitors cilostazol (PDE 3), RO 20-1724 (PDE 4) and sildenafil (PDE 5) were examined in a murine model of allergic asthma. These compounds were used alone and in combination to determine any potential synergism, with dexamethasone included as a positive control. METHODS: Control and ovalbumin sensitised Balb/C mice were administered orally with each of the possible combinations of drugs at a dose of 3 mg/Kg for 10 days. RESULTS: When used alone, RO 20-1724 significantly reduced eosinophil influx into lungs and lowered tumour necrosis factor-α, interleukin-4 and interleukin-5 levels in the bronchoalveolar lavage fluid when compared to untreated mice. Treatment with cilostazol or sildenafil did not significantly inhibit any markers of inflammation measured. Combining any of these PDE inhibitors produced no additive or synergistic effects. Indeed, the anti-inflammatory effects of RO 20-1724 were attenuated by co-administration of either cilostazol or sildenafil. CONCLUSIONS: These results suggest that concurrent treatment with a PDE 3 and/or PDE 5 inhibitor will reduce the anti-inflammatory effectiveness of a PDE 4 inhibitor.